Volume 2A: Turbomachinery 2019
DOI: 10.1115/gt2019-90471
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Design Investigation of a Turbofan in Distorted Inlet Conditions

Abstract: Designing a turbofan to operate in distorted inlet conditions is an issue of growing interest. In such conditions however, fan design can be computationally challenging. Indeed, subject to neither axi-symmetrical nor periodic inlet conditions, computations must be carried out throughout the whole circumferential domain i.e. 360°. Besides, the classical CFD approach implies the use of URANS computations so as to capture the distortion transfer across the fan stage. Eventually, computations are too onerous to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…The body force strongly overestimates the force at the trailing edge. Similar results have already been observed by Godard [15]. These discrepancies are attributed to the inability of the body force methods to capture the shocks.…”
Section: Steady Comparisonsupporting
confidence: 86%
See 2 more Smart Citations
“…The body force strongly overestimates the force at the trailing edge. Similar results have already been observed by Godard [15]. These discrepancies are attributed to the inability of the body force methods to capture the shocks.…”
Section: Steady Comparisonsupporting
confidence: 86%
“…Thollet [13], with his body force model based on a Lift/Drag analogy and using Kotapalli's [14] body force modeling of metallic blockage, showed in his thesis that his model correctly captures the effect of decreased intake length on flow separation delay on the intake lip. Godard [15] presented a body force methodology for fan blade design under distorted conditions. In his study, Godard showed that body force calculations have significantly smaller restitution time compared to classic U-RANS calculations, with a difference of two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the simulations are limited to a specified range of operating conditions. New developments in parallel force models have been implemented for nonuniform inflows in fans by using a simple empirical-based correlated model for turbulent flow over a flat plate [15,16]. The model used in the two latter references does not include the momentum thickness Reynolds number which is relevant when the flow is separated on the blade.…”
Section: Introductionmentioning
confidence: 99%
“…However, designing a fan in BLI conditions is a real challenge. Nevertheless, several authors have already managed to draw some guidelines using both low-fidelity methods [24,25] or more advanced unsteady approaches. In particular, fan design in BLI conditions must account for non-axisymetric inflows, which can be partially addressed by non-axisymetric components (ex.…”
mentioning
confidence: 99%